Tindak Tutur Langsung dan Tidak Langsung dalam Jual Beli di Pasar Kedungsukun dan Implikasinya terhadap Pembelajaran di SMA - Alsun Amini; Syamsul Anwar; Wahyu Asriyani (Journal on Education, 2023)
The purpose of this study is to describe: 1) direct speech acts in buying and selling transactions at the Kedungsukun Market, 2) indirect speech acts contained in buying and selling transactions at the Kedungsukun Market, 3) to describe the implications of research results on learning in high school. The approach in this study uses a qualitative approach, the source of the data used is in the form of speech quotes spoken by buyers to traders or vice versa. The data collection technique used in this research uses observation techniques, interview techniques, recording techniques, and listening and note-taking techniques. The data analysis technique in this study is direct and indirect speech from the object of research. The results showed: 1) the types of direct and indirect speech acts contained in buying and selling transactions at the Kedungukun Market include: 1) direct and indirect speech acts with news sentences (declarative), direct and indirect speech acts with interrogaive sentences (interrogative). , direct and indirect speech acts with imperative sentences, 2) implications of learning Indonesian in SMA class X in KD. 3.1 Understand the structure and rules of negotiating texts both orally and in writing. At KD. 3.1.1 Analyzing the structure and rules of the negotiation text both orally and in writing.